2011
DOI: 10.1042/cs20110108
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell injection ameliorates chronic renal failure in a rat model

Abstract: CKD (chronic kidney disease) has become a public health problem. The therapeutic approaches have been able to reduce proteinuria, but have not been successful in limiting disease progression. In this setting, cell therapies associated with regenerative effects are attracting increasing interest. We evaluated the effect of MSC (mesenchymal stem cells) on the progression of CKD and the expression of molecular biomarkers associated with regenerative effects. Adult male Sprague-Dawley rats subjected to 5/6 NPX (ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 51 publications
5
58
1
12
Order By: Relevance
“…Dosing was based on similar published manuscripts. 12,13 Sections of bladder tissue were fixed in 4% paraformaldehyde. Paraffin blocks were prepared with xylene and alcohol, washed with phosphate-buffered saline (PBS), and mounted using 4-feet 6-diamidino-2-phenylindole (DAPI) containing mounting-solution (ProLong Gold Antifade mounting medium, Invitrogen, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Dosing was based on similar published manuscripts. 12,13 Sections of bladder tissue were fixed in 4% paraformaldehyde. Paraffin blocks were prepared with xylene and alcohol, washed with phosphate-buffered saline (PBS), and mounted using 4-feet 6-diamidino-2-phenylindole (DAPI) containing mounting-solution (ProLong Gold Antifade mounting medium, Invitrogen, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…In an eff ort to address the mechanisms involved in the amelioration of renal disease induced by MSCs, we recently evaluated several functional and molecular markers of kidney damage and regeneration in rats subjected to 5/6 nephrectomy (NPX) (Villanueva et al, 2011). In this well known model of chronic kidney disease, a single intravenous infusion of 0.5×10 6 MSCs was associated with significant reduction of serum creatinine and infl ammatory markers including macrophage infi ltration and interstitial α-SMA (α-smooth muscle actin).…”
Section: Msc Paracrine Factors In the Repair Mechanismmentioning
confidence: 99%
“…A number of studies have hypothesised that certain growth factors or specific hormones, including HGF, EGF and IGF-1, are able to promote this transformation process, and accelerate the differentiation of nascent epithelial cells (30)(31)(32). In addition, several scholars have demonstrated that BMSCs are able to secrete a number of cytokines, thereby promoting the proliferation and repair of the endogenous renal tubular epithelial cells (33,34).…”
Section: Discussionmentioning
confidence: 99%